Pengaruh Kondisi Main Jet Karburator terhadap Konsumsi Bahan Bakar pada Mesin Bensin Empat Langkah 125 cc: A Systematic Literature Review - Rozy, Fakhrur; Doni, Rahma; Pangaribuan, Rikki Paul; Sinaga, Riyando Samuel; Bahar, Andi (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Constant Velocity (CV) carburetors remain widely used in 125 cc four-stroke gasoline engines; consequently, the condition of the main jet is a critical factor influencing fuel consumption efficiency. While various studies have examined the impact of main jet condition and size on fuel consumption and engine performance, the findings remain fragmented, lacking a comprehensive overview. Therefore, this study aims to synthesize scientific evidence regarding the effect of carburetor main jet condition on fuel consumption in 125 cc four-stroke gasoline engines. A Systematic Literature Review (SLR) method was employed, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were conducted across Google Scholar, Garuda, and Scopus databases using predefined keywords. Fifty articles were initially identified; following a screening process based on inclusion and exclusion criteria, 20 articles were selected for analysis using a narrative synthesis approach. The review results indicate that main jet condition and size influence the air-fuel ratio, combustion efficiency, and fuel consumption. Main jets meeting manufacturer specifications facilitate optimal combustion, thereby enhancing fuel consumption efficiency; conversely, clogging or alterations in main jet size disrupt the air-fuel mixture balance, leading to increased fuel consumption and reduced engine performance. The novelty of this study lies in its comprehensive synthesis of research findings concerning the relationships between main jet condition, clogging mechanisms, combustion characteristics, and fuel consumption in 125 cc four-stroke gasoline engines. These findings are expected to serve as a scientific reference for future research and provide a basis for developing maintenance strategies and optimizing carburetor systems to improve fuel consumption efficiency.